The Role of Teachers in Building Character Caring for the Environment for Students of SMPIT Nurul Fikri Boarding School Aceh - Ruliani, Ruliani; Abdi, Abdul Wahab; Gadeng, Ahmad Nubli (Jurnal Pendidikan Ilmu Sosial, 2023)
Teachers have an important role in shaping the character of students. So the purpose of this study is to (1) determine the role of teachers in building character, (2) determine the level of environmental care for students. This study uses a quantitative descriptive method. The entire research population was 25 teachers and 267 students in grades VII-IX. Sampling with random sampling technique. Data were collected by distributing questionnaires to respondents. Data were analyzed by descriptive statistical percentage formula. The results of data processing obtained: from 25 teachers, it is known that 2 respondents (8%) in very high category, 6 respondents (24%) in high category, 12 respondents (48%) in medium category, 1 respondent (4%) in low category, and 4 respondents (16%) are very low, so that the teacher's role in the formation of environmental character is the largest in the category. (2) Of the 50 students, 6 respondents (12%) were in the very high category, 7 respondents (14%) were in the high category, 22 respondents (44%) were in the medium category, 12 respondents (24%) were in the low category, and 3 respondents (6%) ) ) category is very low, so that the main environmental care level is in the medium category.